Case Report: Prevention of Rhabdomyolysis-Associated Acute Kidney Injury by Extracorporeal Blood Purification With Cytosorb® - Rauch, Simon; Borgato, Andrea; Gruber, Ewald; Leggieri, Carlo; Bock, Matthias; Seraglio, Paolo Mario Enrico (Frontiers in Pediatrics, 2022)
Acute kidney injury (AKI) is a severe complication of rhabdomyolysis. The pathophysiology of rhabdomyolysis-associated AKI is complex, but myoglobin related damage plays a major role. Extracorporeal removal of myoglobin is therefore an appealing target to prevent AKI, however, attempts to remove myoglobin with standard dialysis membranes have so far been disappointing. Here we report the case of a 12-year-old boy with severe trauma-related rhabdomyolysis where we successfully utilized continuous renal replacement therapy in combination with Cytosorb® to eliminate myoglobin and prevent AKI. The early use of extracorporeal myoglobin removal with Cytosorb® after severe rhabdomyolysis might be an option and should be further investigated as a tool to prevent the development of AKI.